DIGITALISASI ADMINISTRASI SEKOLAH - Nuraini Nuraini (Jurnal Komunikasi, 2024)
In the digital era, every school is required to provide complete and fast information for parents, students and teachers as well as all school administrators. Complete and fast information will of course benefit the school. With information system technology, schools can be more effective, efficient, accountable and transparent. A school administration system that can be accessed by all school members, including teachers, school staff, parents and students, makes integrated communication easier. The stages in or how schools start using digital administration may vary from one school to another, the steps for schools to start digital administration are to prepare the software and skills of operational personnel who need to be trained in using it or make the application as attractive as possible and designing a clear flow of each unit in the school. The support needed by schools to create schools with orderly digital-based administration with the support of operators and teachers who understand the use and workings of digital-based administration, one of the efforts that must be made by schools is by providing training for operators and teachers as well as all elements who are involved in school. There are administrations that can be started by schools for school administration, school program systems, teaching material platform systems or teaching materials, online-based teacher and student attendance systems, online- based guest book systems, online-based book borrowing systems, online-based new student registration systems, payment systems. online-based school fees, application or platform-based teacher administration systems and online-based assessment systems